Opening the doors: inclusive creative projects and community engagement in Spanish museums - Rojas-Pernia, Susana; Sanahuja-Gavaldà, Josep M.; Macho de Cos, Isabel; Montero-Camacho, Mario (Frontiers in Education, 2025)
Participation in culture is a human right. Close collaboration between social, educational and cultural institutions can facilitate access for all members of the community and open new social and educational spaces for those whose right to participate in cultural life has been violated. As part of a European project to promote social inclusion through the arts, this article describes and analyzes two Inclusive Creative Projects (ICP) carried out by social, educational and cultural centers. These collaborative projects were created with the objective of analyzing the key elements to promote inclusion through art and artistic creation in museums. Students from primary and special education schools (n = 74) and adults with intellectual disabilities (n = 12) participated in the two projects. Additionally, staff from arts institutions (n = 12) and socio-educational centers (n = 10), creating spaces for dialogue, reflection and learning in an inclusive context. Qualitative and ethnographic techniques were used to document the process of designing and implementing the projects. Through the field diaries, which included field notes and photographs, the set of visual and creative techniques used to explore personal experiences and the development of the ICPs were recorded. The findings underscore the need to create projects that recognize diversity as an intrinsic characteristic of any human group. They also open avenues for collaboration based on respect and recognition of different skills, experiences and professional trajectories. The projects created spaces for dialogue and learning from and with personal experience, emphasizing processes rather than outcomes. They highlight the need to promote the use of different artistic languages in the creation of inclusive artistic projects, as well as real accessibility. Although implementing the project was complex, collaboration between institutions facilitated the creation of networks that promote professional development and contribute to the development of fairer and more equitable communities.